GORDON ALLPORT’S PSYCHOLOGICAL ANALYSIS IN THE MAIN CHARACTERS OF “MEMOIRS OF A GEISHA” BY ARTHUR GOLDEN - Alifatuz Zhain Intikah; Bambang Yulianto; Elisa Nurul Laili (Universitas Samudra, 2020)
Abstract The novel